Exponent Rules
Exponent rules are those laws which are used for simplifying expressions with exponents. Many arithmetic operations like addition, subtraction, multiplication, and division can be conveniently performed in quick steps using the laws of exponents. These rules also help in simplifying numbers with complex powers involving fractions, decimals, and roots.
Let us learn more about the different rules of exponents, involving different kinds of numbers for the base and exponents.
1.  What are Exponent Rules? 
2.  Laws of Exponents 
3.  FAQs on Exponent Rules 
What are Exponent Rules?
Exponent rules, which are also known as the 'laws of exponents' or the 'properties of exponents' make the process of simplifying expressions easier. These rules are helpful to simplify the expressions that have decimals, fractions, irrational numbers, and negative integers as their exponents.
For example, if we need to solve 3^{4} × 3^{2}, we can easily do it using one of the exponent rules which says, a^{m} × a^{n} = a^{m + n}. Using this rule, we will just add the exponents to get the answer, while the base remains the same, that is, 3^{4} × 3^{2} = 3^{4 + 2} = 3^{6}. Similarly, expressions with higher values of exponents can be conveniently solved with the help of the exponent rules.
Laws of Exponents
The different 'rules and laws of exponents' are also known as the 'properties of exponents'. A few of them are listed as follows: the product rule of exponents, the quotient rule of exponents, the zero rule of exponents, and the negative rule of exponents. Let us learn each of these in detail now.
Product Law of Exponents
The product rule of exponents is used to multiply expressions with the same bases. This rule says, "To multiply two expressions with the same base, add the exponents while keeping the base the same." This rule involves adding exponents with the same base. Here the rule is useful to simplify two expressions with a multiplication operation between them.
Observe the following example.
Using the law  Without using the law 
2^{3} × 2^{5} = 2^{(3 + 5)} = 2^{8}  2^{3} × 2^{5} = (2 × 2 × 2) × (2 × 2 × 2 × 2 × 2) = 2^{8} 
This shows that without using the law, the expression involves more calculation.
Quotient Law of Exponents
The quotient property of exponents is used to divide expressions with the same bases. This property says, "To divide two expressions with the same base, subtract the exponents while keeping the base same." This is helpful in solving an expression, without actually performing the division process. The only condition that is required is that the two expressions should have the same base.
Here is an example.
Using the law  Without using the law 
2^{5}/2^{3} = 2^{5  3} = 2^{2}  2^{5}/2^{3} = (2 × 2 × 2 × 2 × 2)/(2 × 2 × 2 ) = 2^{2} 
We can clearly see that without using the law, the expression involves more calculation.
Zero Law of Exponents
The zero property of exponents is applied when the exponent of an expression is 0. This property says, "Any number (other than 0) raised to 0 is 1." Note that 0^{0} is not defined. The will help us understand that irrespective of the base the value for a zero exponent is always equal to 1.
Here is an example.
Using the law  Without using the law 
2^{0} = 1  2^{0} = 2^{5  5}^{ }= 2^{5}/2^{5} = (2 × 2 × 2 × 2 × 2)/(2 × 2 × 2 × 2 × 2) = 1 
Using the law we simply get 2^{0} = 1. Alternatively, without using the law we can understand the same law with more number of steps: 2^{0} = 2^{5  5}^{ }= 2^{5}/2^{5} = (2 × 2 × 2 × 2 × 2)/(2 × 2 × 2 × 2 × 2) = 1
Negative Law of Exponents
The negative property of exponents is used when an exponent is a negative number. This property says, "To convert any negative exponent into positive exponent, the reciprocal should be taken." The expression is transferred from the numerator to the denominator with the change in sign of the exponent values.
Here is an example.
Using the law  Without using the law 
2^{2} = 1/(2)^{2}  2^{2} = 2^{02} = 2^{0}/2^{2} = 1/(2)^{2} 
Using the law, we can solve it in just one go, like 2^{2} = 1/(2)^{2}. Alternatively, without using the law we have 2^{2} = 2^{02} = 2^{0}/2^{2} = 1/2^{2}
Power of a Power Law of Exponents
The 'power of a power property of exponents' is used to simplify expressions of the form (a^{m})^{n}. This property says, "When we have a single base with two exponents, just multiply the exponents." The two exponents are available one over the other. These can be conveniently multiplied to make a single exponent.
Here is an example.
Using the law  Without using the law 
(2^{2})^{3} = 2^{6}  (2^{2})^{3} =(2^{2}).(2^{2}).(2^{2}) =(2.2).(2.2).(2.2) = 2^{6} 
Using the law, (2^{2})^{3} = 2^{6}, whereas, the same thing without the exponent rules take more steps and is expressed as (2^{2})^{3} =(2^{2}).(2^{2}).(2^{2}) =(2.2).(2.2).(2.2) = 2^{6}
Power of Product Rule of Exponents
The 'power of a product property of exponents' is used to find the result of a product that is raised to an exponent. This property says, "Distribute the exponent to each multiplicand of the product."
Here is an example.
Using the law  Without using the law 
(xy)^{3} = x^{3}.y^{3}  (xy)^{3} =(xy).(xy).(xy) = (x.x.x).(y.y.y) x^{3}.y^{3} 
Using the law, (xy)^{3} = x^{3}.y^{3}. On the other hand, the same thing can be expressed in multiple steps, without using the law. (xy)^{3} =(xy).(xy).(xy) = (x.x.x).(y.y.y) x^{3}.y^{3}
Power of a Quotient Rule of Exponents
The power of a quotient property of exponents is used to find the result of a quotient that is raised to an exponent. This property says, "Distribute the exponent to both the numerator and the denominator." Here, the bases are different and the exponents are the same for both the bases.
Here is an example of the exponent rule given above.
Using the law  Without using the law 
(x/y)^{3} = x^{3}/y^{3}  (x/y)^{3} = x/y . x/y . x/y = x^{3}/y^{3} 
We can use the law and simply solve it as, (x/y)^{3} = x^{3}/y^{3}, and we can also solve the same expression without the law which involves multiple steps. (x/y)^{3} = x/y . x/y. x/y = x^{3}/y^{3}.
Exponent Rules Chart
The rules of exponents explained above can be summarized in a chart as shown below.
Zero Exponent Rule  a^{0} = 1 
Identity Exponent Rule  a^{1} = a 
Product Rule  a^{m} × a^{n} = a^{m+n} 
Quotient Rule  a^{m}/a^{n }= a^{mn} 
Negative Exponents Rule  a^{m} = 1/a^{m}; (a/b)^{m} = (b/a)^{m} 
Power of a Power Rule  (a^{m})^{n} = a^{mn} 
Power of a Product Rule  (ab)^{m} = a^{m}b^{m} 
Power of a Quotient Rule  (a/b)^{m} = a^{m}/b^{m} 
Tips on Laws of Exponents
 If a fraction has a negative exponent, then we take the reciprocal of the fraction to make the exponent positive, i.e., (a/b)^{m} = (b/a)^{m}
 We can convert a radical into an exponent using the following property: a^{1/n} = \(\sqrt[n]{a}\)
☛ Related Articles
Exponent Rules Examples

Example 1: Solve the expression using the exponent rules: 10^{3} × 10^{4}
Solution:
According to the exponent rules, to multiply two expressions with the same base, we add the exponents while the base remains the same. This means, 10^{3} × 10^{4} = 10^{(3 + 4)} = 10^{1} = 10

Example 2: Solve the given expression and select the correct option using the laws of exponents: 10^{15} ÷ 10^{7}
a.) 10^{8}
b.) 10^{22}
Solution:
As per the exponent rules, when we divide two expressions with the same base, we subtract the exponents. This means, 10^{15}/10^{7}= 10^{15  7} = 10^{8}.
Therefore, the correct option is (a) 10^{8}

Example 3: Using the rules of exponents, state whether the following statements are true or false.
a.) If a fraction has a negative exponent, then we take the reciprocal of the fraction to make the exponent positive, i.e., (a/b)^{m} = (b/a)^{m}
b.) 672^{0} = 0
Solution:
a.) True, if a fraction has a negative exponent, then we take the reciprocal of the fraction to make the exponent positive, i.e., (a/b)^{m} = (b/a)^{m}
b.) False, according to the zero rule of exponents, any number to the power of zero is always equal to 1. So, 672^{0} = 1
FAQs on Exponent Rules
What are Exponent Rules in Math?
Exponent rules are those laws which are used for simplifying expressions with exponents. These laws are also helpful to simplify the expressions that have decimals, fractions, irrational numbers, and negative integers as their exponents. For example, if we need to solve 34^{5} × 34^{7}, we can use the exponent rule which says, a^{m }× a^{n }= a^{m+n}, that is, 34^{5} × 34^{7} = 34^{5 + 7} = 34^{12 }. A few rules of exponents are listed as follows: Product Rule: a^{m }× a^{n }= a^{m+n}; Quotient Rule: a^{m}/a^{n }= a^{mn}; Negative Exponents Rule: a^{m }= 1/a^{m}; Power of a Power Rule: (a^{m})^{n }= a^{mn}.
What are the 8 Laws of Exponents?
The 8 laws of exponents can be listed as follows:
 Zero Exponent Law: a^{0 }= 1
 Identity Exponent Law: a^{1 }= a
 Product Law: a^{m }× a^{n }= a^{m+n}
 Quotient Law: a^{m}/a^{n }= a^{mn}
 Negative Exponents Law: a^{m }= 1/a^{m}
 Power of a Power: (a^{m})^{n }= a^{mn}
 Power of a Product: (ab)^{m }= a^{m}b^{m}
 Power of a Quotient: (a/b)^{m }= a^{m}/b^{m}
What is the Purpose of the Exponent Rules?
The purpose of exponent rules is to simplify the exponential expressions in fewer steps. For example, without using the exponent rules, the expression 2^{3} × 2^{5} is written as (2 × 2 × 2) × (2 × 2 × 2 × 2 × 2) = 2^{8}. Now, with the help of exponent rules, this can be simplified in just two steps as 2^{3} × 2^{5} = 2^{(3 + 5)} = 2^{8}.
How to Prove the Rules of Exponents?
The exponent rules can be proved easily by expanding the terms. The exponential expression is expanded by writing the base as many times as the power value. The exponent of the form a^{n} is written as a × a × a × a × a × .... n times. Further, on multiplying we can obtain the final value of the exponent. For example, let us solve 4^{2} × 4^{4}. Using the 'product law' of exponents, which says a^{m }× a^{n }= a^{m+n}, we get 4^{2} × 4^{4} = 4^{2 + 4} = 4^{6}. This can be expanded and checked as (4 × 4) × (4 × 4 × 4 × 4) = 4096. We know that the value of 4^{6} is also 4096. Hence, the exponent rules can be proved by expanding the given terms.
What are the Exponent Rules when Bases are the same?
When the bases are the same, all the laws of exponents can be applied. For example, to solve 3^{12} ÷ 3^{4}, we can apply the 'Quotient Rule' of exponents in which the exponents are subtracted. So, 3^{12} ÷ 3^{4} will become 3^{124} = 3^{8}. Similarly, to solve 4^{9} × 4^{4}, we apply the 'Product Rule' of exponents in which the exponents are added. This will result in 4^{9+4} = 4^{13}.
What are the Exponent Rules when Bases are Different?
When the bases and powers are different, then each term is solved separately and then we move to the further calculation. For example, let us add 4^{2} + 2^{5 }= (4 × 4) + (2 × 2 × 2 × 2 × 2) = 16 + 32 = 48. This exponent rule is applicable to addition, subtraction, multiplication, and division. In another example, if the expressions with different bases and different powers are multiplied, each term is evaluated separately and then multiplied. This can be represented as a^{n} × b^{m }= (a^{n}) × (b^{m}). For example, 10^{3} × 6^{2 }= 1000 × 36 = 36000.
What is the Rule for Zero Exponents?
The rule of zero exponents is a^{0} = 1. Here, 'a', which is the base can be any number other than 0. This property says, "Any number (other than 0) raised to 0 is 1." For example, 5^{0} = 1, x^{0} = 1 and 23^{0} = 1. However, it should be noted that 0^{0} is not defined.
What is the Difference Between Exponents and Powers?
Exponents and powers refer to the same term. A number of the form a^{m} has the base 'a' and the power m. 'm' is also referred to as an exponent.
Can the Exponent be a Fraction?
Yes, the exponent value can be a fraction. The exponent rule relating to the fraction exponent value is (a^{m})^{1/n} = a^{m/n}. This rule is sometimes helpful to simplify and transform a surd into an exponent.
visual curriculum